Quarantined histories: Sindh and the question of historiography in colonial India- Part I - Asif, Manan Ahmed (History compass, 2017)
This essay examines histories of colonial British India and the annexation of Sindh in 1843 from two perspectives. The first is the colonial historiographic project that frames the history of Islam in India, creates an archive for its study and produces the political and military dominance of Sindh. Fundamentally, it argues that Muslims in India cannot produce their own histories for they lack the language and archives for scientific objectivity. In response, a set of Indian intellectuals take on the project of writing histories of Sindh from 1890 to 1950s. These histories are written in direct dialogue with the colonial archive and insist on their engagement with social scientific methodologies and tools. In rethinking this past, the essay argues that that Urdu historiography was itself deemed unscientific by modern South Asian historians and abandoned as not "proper history." This essay thus asks that we incorporate such histories in our genealogies of anticolonial past.